UJI EFEKTIVITAS EKSTRAK DAUN SENDUDUK (Melastoma malabathricum L.) SEBAGAI ANTIBAKTERI Salmonella typhi - samosir, Muhammad Arif Samosir; Almuzafri; Rizah Rizwana Wahyuni (SUNGKAI, 2024)
This research on the effectiveness test of Melastoma malabathricum L. plants as antibacterial agents for Salmonella was conducted from September to October 2023. The purpose of this study was to prove that Senduduk leaf extract (Melastoma malabathricum L.) is effective as an antibacterial against Salmonella typhi. The disc diffusion method was used as an antibacterial fraction to be tested by being absorbed on disc paper, the descriptive method was used to see the antibacterial ability which was arranged based on variations in solutions with 5 treatments in duplicate. Treatment with variations in senduduk leaf extract solutions of 20%, 40%, 60% and 80% and sterile aquadest as a control. The results of the study showed that the Melastoma malabathricum L. plant originating from the land of the Faculty of Agriculture is a plant that has a content in accordance with the phytochemical content described by (Afrianti M, Dwiloka B, Setiani B E, 2013). In The Inhibition Test, The Variation Of The 80% Leaf extract solution produced an inhibition zone with the largest diameter of 18.25 mm, this indicates that the Melastoma malabathricum L. leaf extract has better inhibition compared to the 20%, 40% and 60% leaf extract concentrations.